RESPON PEMBERIAN ZPT GIBERELIN DAN ASAM HUMAT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT CERI - Revina Azhari, Clarisa; Kurniawan, Dedi; Berliana, Yunida (Yayasan Amanah Nur Aman, 2025)
This research was conducted in Medan Marelan District, Medan City, North Sumatra Province. They were starting from January to July 2024. Cherry tomatoes (Solanum lycopersicum var. cerasiforme) are one of the vegetables grown by Indonesian farmers. Cherry tomatoes have great economic value and can not only be used as vegetables but also as raw materials for the pharmaceutical, cosmetic, and food industries. This research aimed to determine the effect of giving several concentrations of gibberellin and humic acid PGRs on the growth and yield of cherry tomato plants. This research used a factorial randomized block design (RAK) consisting of two treatment factors, with the first factor being gibberellin with the symbol (G) consisting of 3 treatment levels, namely: G0 = control, G1 = Gibberellin 10 ml/Liter of water, G2 = Gibberellin 20 ml/Liter of water. The second factor is humic acid with the symbol (A) which consists of 4 levels, namely A0 = control, A1 = 1 gr/Liter of water, A2 = 2 gr/Liter of water, A3 = 3 gr/Liter of water. The parameters observed in this study were plant height (cm), stem diameter (mm), number of branches (bb), flowering age (days), leaf color (bwd), number of fruit per plant (fruit), fruit weight per plant (gr ) and fruit weight per plot (gr). The research results showed that gibberellin treatment had a significant effect on flowering time and the number and weight of fruit on cherry tomato plants. Humic acid treatment has a substantial impact on plant height at 4 WAP, 5 WAP, 6 WAP, and 7 WAP, stem diameter at 4 WAP, 5 WAP, 6 WAP, and 7 WAP. The interaction of the two treatments had a very significant effect on stem diameter at 6 WAP and 7 WAP.